1995
DOI: 10.1111/j.1464-5491.1995.tb02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Plasma Aldosterone Concentrations in Randomly Selected Patients with Insulin‐dependent Diabetes Mellitus

Abstract: Abnormalities of the renin-angiotensin system have been reported in patients with diabetes mellitus and with diabetic complications. In this study, plasma concentrations of prorenin, renin, and aldosterone were measured in a stratified random sample of 110 insulin-dependent (Type 1) diabetic patients attending our outpatient clinic. Fifty-four age- and sex-matched control subjects were also examined. Plasma prorenin concentration was higher in patients without complications than in control subjects when uprigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…We found lower aldosterone levels despite similar PRA, resulting in an increased PRA/aldosterone ratio in type 1 DM, as reported earlier [3,4,6,11]. Notably, in a study in normoalbuminuric type 1 DM with glomerular hyperfiltration, others found an elevated PRA/aldosterone ratio to be the result of an increased PRA with normal aldosterone levels [2].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found lower aldosterone levels despite similar PRA, resulting in an increased PRA/aldosterone ratio in type 1 DM, as reported earlier [3,4,6,11]. Notably, in a study in normoalbuminuric type 1 DM with glomerular hyperfiltration, others found an elevated PRA/aldosterone ratio to be the result of an increased PRA with normal aldosterone levels [2].…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, plasma renin activity (PRA) has been reported to be increased [2,3], unaltered [4–6] or decreased [7,8], whereas plasma aldosterone levels have been reported to be normal [2,9,10], increased [4] or low [6,8,11] in DM. Furthermore, the PRA/aldosterone ratio, as an indicator of aldosterone responsiveness to endogenous renin‐angiotensin action, can be estimated to be increased [2–4,6,11], although a normal [5,8,9] ratio has also been observed. Several factors could be involved in the discrepancies between the above‐mentioned studies, as patients were heterogeneous with respect to the type of DM and the presence of diabetes‐associated complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of angiotensin (Ang) II and its upstream components of the RAS has been complicated by the rapid degradation of these peptides 4,5 and the local regulation of this production within specific vascular tissues and lesions. 6 Therefore, reports on the effects of diabetes on plasma and the tissue RAS, including Ang II levels, are controversial, [7][8][9] and interpretation of these changes is limited by the potential downstream modulation of renin and Ang II production and stability.…”
Section: Clinical Perspective P 1798mentioning
confidence: 99%
“…PRA was reported to be increased [11,12], unaltered [13,[58][59][60][61] or decreased [20] in diabetes mellitus, whereas plasma aldosterone levels have been reported to be normal [11,13,14], increased [12,58] or low [59,62,63]. Furthermore, the PRA/aldosterone ratio, as an indicator of aldosterone responsiveness to endogenous renin-angiotensin action, has been reported to be increased in diabetes mellitus [10,11,58,59,63] although a normal [60,62] ratio has also been reported. In long standing, complicated diabetes mellitus hypo-aldosteronism appears to be linked to hypo-reninism.…”
Section: Changes In the Raas In Diabetes Mellitusmentioning
confidence: 99%